26 Setting up a neurological prognostication service in a tertiary cardiothoracic centre with no neuro-physiology service. (27th November 2017) - Potter, Matt; Watson, Noel; Maccoroni, Maria; Karamasis, Grigoris; Al-Janabi, Firas; Damian, Max; Cumbers, Jenny; Pottinger, Richard; Davies, John; Keeble, Thomas
Abstract : Background: Brain injury due to hypoxia, is the most common cause of mortality in patients that have been successfully resuscitated following Cardiac Arrest. The Essex Cardiothoracic Centre (CTC) is a tertiary cardiac centre where all cardiac arrest patients are triaged on arrival within the catheter lab. Here there is access to appropriate PCI and mild therapeutic hypothermia (32°C–33°C), which has increased the survival rate to 67% of all out of hospital arrest patients. Methods and results: Previously the CTC has relied upon neurological clinical examination and CT for neurological prognostication, neither of which are appropriate for all patients. In 2014 the ERC and ESICM, suggest the use of a multimodal approach in normothermic and hypothermic patients. We aimed to test the feasibility of setting up a neurological prognostication service using a multimodal approach, with the use of EEG, SSEP and Biomarkers. We believe that by adhering to strict criteria, a multimodal approach can be used safely and effectively in a Cardiac Centre with no on-site neurophysiological support, for more accurate neurological prognostication. The staff have been trained over a 3 month period by external neurophysiology experts to record high quality 20 min EEG, sent to a core lab for analysis and SSEP, interpreted locally. Biomarkers are sent to a reference lab. Conclusion: This feasibility study has shown that senior ICU staff can be trained in EEG/SSEP recordings, and can then be interpreted rapidly in a core lab to allow neuro-prognostication to occur in all cardiac centres. This is vital for the up-coming TTM2 trial in 2017.